Model pendampingan dinas sosial dalam menurunkan tingkat kekerasan terhadap anak - Abu Nawar; Joko Setyoko (Jurnal Politik dan Pemerintahan Daerah, 2019)
The purpose of this research is to find out the assistance model of the Social Service for Population Control for Family Planning for Women's Empowerment and Child Protection (Dinsos P2KBP3A) in reducing the level of violence against children in Bungo District. The method used in this study is a qualitative research method that is descriptive in nature. The method used in this study is a qualitative research method that is descriptive in nature. The informant selection technique used by researchers in this study is to use a purposive sampling method (sampling technique with certain considerations). The results of this study indicate that the Mentoring Model conducted by the Social Service is a form of assistance in the form of budgets and policies, but for the implementation of direct assistance to children as victims of violence carried out by the Integrated Service Center for Empowering Women and Children (P2TP2A), some assistance is carried out by P2TP2A against child victims of violence, namely medical assistance, psychological assistance, and juridical assistance. Some of the obstacles experienced by the Social Service Population Control Family Planning for Women's Empowerment and Child Protection (Dinsos P2KBP3A) in reducing the level of violence against children in Bungo District, including the lack of community and parental knowledge about violence against children and the lack of community participation in reporting incidents of violence in children. The Efforts of the Social Service for Population Control of Family Planning for Women's Empowerment and Child Protection (Dinsos P2KBP3A) in overcoming obstacles to reducing the level of violence against children in Bungo District, including increasing socialization to the community and providing safe houses.AbstrakPenelitian ini bertujuan untuk mengetahui model pendampingan Dinas Sosial Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak (Dinsos P2KBP3A) dalam menurunkan tingkat kekerasan terhadap anak di Kabupaten Bungo. Pendekatan penelitian ini menggunakan metode deskriptif kualitatif. Teknik pemilihan informan yang digunakan yaitu menggunakan metode purposive sampling (teknik penentuan sampel dengan pertimbangan tertentu). Hasil penelitian ini menunjukkan bahwa Model pendampingan yang dilakukan Dinas Sosial merupakan pendampingan dalam bentuk anggaran dan kebijakan, namun untuk pelaksanaan pendampingan secara langsung terhadap anak sebagai korban tindak kekerasan dilakukan oleh Pusat Pelayanan Terpadu Pemberdayaan Perempuan dan Anak (P2TP2A). Beberapa pendampingan yang dilakukan P2TP2A terhadap anak korban kekerasan yaitu pendampingan medis, pendampingan psikologis, dan pendampingan yuridis. Adapun hambatan yang dialami Dinas Sosial Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak (Dinsos P2KBP3A) dalam menurunkan tingkat kekerasan terhadap anak di Kabupaten Bungo, diantaranya adalah minimnya Pengetahuan masyarakat dan orang tua tentang Kekerasan terhadap anak dan minimnya partisipasi masyarakat dalam melaporkan kejadian tindak kekerasan pada anak. Upaya Dinas Sosial Pengendalian Penduduk Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak (Dinsos P2KBP3A) dalam mengatasi hambatan untuk menurunkan tingkat kekerasan terhadap anak di Kabupaten Bungo, diantaranya adalah meningkatkan intensitas sosialisasi kepada masyarakat dan penyediaan rumah aman ramah anak.